Peaceful Coexistence in Christian Schools in Kurdistan Region of Iraq - Bestun Omer Ali Surchi; Iyad M. Eid; Nurazzura Mohamad Diah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The importance of ethnic and religious variety in educational settings is highlighted in this study, which examines the dynamics of peaceful coexistence in Christian schools in the Kurdistan Region of Iraq. It looks at the chances and difficulties that minority Christian students—Chaldean, Assyrian, and Armenian—present in a setting that is primarily Muslim and Kurdish. The study makes the case that these institutions work as microcosms of integration and tolerance, encouraging constructive relationships between students and instructors from different backgrounds in spite of larger social conflicts. The study's qualitative data collection from educators, parents, and students shows a generally peaceful atmosphere with little prejudice and respect for ethnic and religious identities. Such inclusive practices may be used as a model for resolving ethnic and religious disputes in the area and beyond, according to the paper, which highlight the importance of education in fostering mutual understanding and peace. In the end, this paper supports ongoing initiatives to promote harmonious cohabitation through fair educational laws and curriculum that value and celebrate individuality.